ESTROUS OF GOATS UNDERGONE SUPEROVULATION INDUCTION WITH ANTI-INHIBIN - Siregar, TN; Armansyah, T (ANIMAL PRODUCTION, 2009)
Estrous performance of goats underlying superovulation induction with anti-inhibin was done using anti-inhibin induction on rabbit. Twenty four goats used in this research that divided four groups namely P0 (control), P1 (immunization at days of 4 cycle), P2 (immunization at days of 9 cycle)  and P3 (immunization at days of 13 cycle). Immunization on groups was done with injection of 500 ?g antibody against inhibin after synchronize before that. Estrous synchronization using injection 0.5 ml cloprostenol  (EstronTM, Bioveta) two times with interval 10 days. Twenty four hours after immunization, all of goats injection of cloprostenol with same doses. Estrous observation was done after injection of cloprostenol later three times a days. Collection of blood was done at estrous (to analyze of estradiol concentration) and at days of 7 cycle (to analyze of progesterone concentration). All f goats after treatment showed estrous behavior as swelling around the vulva and redness, a thin mucous discharge from vulva, social behaviors, and showed mounted. Awal of estrous on P0, P1, P2, and P3 groups were  35.00+7.01; 28.67+4,50; 27.67+4.76; and 29.67+5.86 hours, respectively and revealed no significant difference between control and treatment groups. Duration of estrous on P0, P1, P2, and P3 were 36.67+3.27; 49.33+3.20; 50.33+10.23; and 53.67+11.96 hours, respectively and revealed significant difference (P<0.05) between P2 and P3 with P0 and P1. Length of cycle on  P0, P1, P2, and P3 groups were  20.33+1.75; 19.33+0.82; 19.33+2.50; and 20.83+2.56, respectively and revealed no significant difference between control and treatment groups. (Animal Production 11(1): 34-39 (2009) Key Words: anti-inhibin, goats, superovulation, synchronization